Tuberculosis and HIV coinfection and related collaborative activities in Latin America and the Caribbean - Ralfh Moreno; Giovanni Ravasi; Pedro Avedillo; Rafael Lopez (Pan American Health Organization, 2020)
Objective. To inform about the most recent epidemiological trends and integrated programmatic response to tuberculosis (TB) and HIV coinfection in Latin America and the Caribbean (LAC). Methods. A descriptive review analyzed the most relevant indicators on TB/HIV coinfection in 33 countries in LAC with a cross-sectional and time-trend approach. Data were obtained from publicly available databases and analyzed through simple proportions, weighted means, and risk ratios. Results. In LAC, during 2017, 80.8% of TB patients were actively screened for HIV, with a 25.6% increase between 2011 and 2017. In the same year, the proportion of TB patients with HIV-positive status was 11.2%, with a small but progressive reduction of 5% since 2011. The provision of antiretroviral therapy and anti-TB medication among TB/HIV coinfected patients for 2017 was at 60%. Only one-third of people living with HIV had access to isoniazid preventive therapy. Overall, the mortality in the TB/HIV cohort has not changed since 2012, hovering at around 20%. Conclusions. TB/HIV collaborative activities, as the backbone to address TB/HIV coinfection, are being scaled up in LAC and some indicators show a tendency toward improvement; nevertheless, our review shed light on the need to keep strengthening integration of service delivery, joint monitoring and evaluation, and data quality.